An alternative route to the arylvinyltriazole nucleosides. Issue 14 (15th July 2016) - Chudinov, Mikhail V.; Prutkov, Alexander N.; Matveev, Andrey V.; Grebenkina, Lyubov E.; Konstantinova, Irina D.; Berezovskaya, Yulia V.
Graphical abstract: Abstract: A new pathway to synthesis of arylvinyl ribavirin analogues is developed which makes it possible to obtain not only trans - but also cis -isomers at vinyl bond. By this route eight ribavirin 5-arylvinyl analogues are synthesized and their antiviral activity is evaluated.